Proceedings of the 17th International Conference on Human-Computer Interaction With Mobile Devices and Services 2015
DOI: 10.1145/2785830.2785873
|View full text |Cite
|
Sign up to set email alerts
|

GazeNav

Abstract: Pedestrian navigation systems help us make a series of decisions that lead us to a destination. Most current pedestrian navigation systems communicate using map-based turn-byturn instructions. This interaction mode suffers from ambiguity, its user's ability to match the instruction with the environment, and it requires a redirection of visual attention from the environment to the screen. In this paper we present GazeNav, a novel gaze-based approach for pedestrian navigation. GazeNav communicates the route to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Step 1: Prepare Input Data In this initial step, the video recordings and associated gaze data are prepared by identifying the fixation points, as outlined in Figure 1, step A. We used the IDT (Identification by Dispersion-Threshold) algorithm by [39] as a commonly used dispersion-based algorithm to detect fixations (gaze-dispersion threshold: 0.02 deg; time threshold: 100 ms [40]). However, any other applicable fixation detection algorithm can be seamlessly integrated into this process, provided that the algorithm's output conforms to the necessary format.…”
Section: Myfix: Mask2former-yolo Fixation Annotation Pipelinementioning
confidence: 99%
“…Step 1: Prepare Input Data In this initial step, the video recordings and associated gaze data are prepared by identifying the fixation points, as outlined in Figure 1, step A. We used the IDT (Identification by Dispersion-Threshold) algorithm by [39] as a commonly used dispersion-based algorithm to detect fixations (gaze-dispersion threshold: 0.02 deg; time threshold: 100 ms [40]). However, any other applicable fixation detection algorithm can be seamlessly integrated into this process, provided that the algorithm's output conforms to the necessary format.…”
Section: Myfix: Mask2former-yolo Fixation Annotation Pipelinementioning
confidence: 99%
“…Even though map-less interaction principles for spatial decision situations have been proposed (e.g., [16,39,46]), map interfaces are still one of the most frequently used mobile interface types, and novel approaches to map interaction are actively discussed in the HCI community (e.g., [28,32,34,55,58]).…”
Section: Mobile Map Adaptationmentioning
confidence: 99%
“…Elias, Hampe and Sester (2005), Gartner et al (2011), , Röser et al (2012) and Sarjakoski and Nivala (2005) suggested landmarks appropriate for use in navigating could be selected as features the map user should look for. In addition, haptic feedback could be employed to alert the user of a map on a smartphone or other digital device that they are approaching a landmark or a decision-making location (Giannopoulos, Kiefer & Raubal 2015;Me, Biamonti & Saad 2015). This would allow the user to keep their gaze and attention on the environment around them, rather than on the map, therefore building their spatial knowledge acquisition.…”
Section: Key Finding 1: Looking At the Map Frequently Caused Particip...mentioning
confidence: 99%
“…The concurrent think aloud technique provided additional information about what participants were thinking while they were completing the activities. These techniques have been applied in similar studies (Giannopoulos, Kiefer & Raubal 2015;Keil et al 2020;Kiefer, Giannopoulos & Raubal 2014).…”
Section: Figure 6-6 Photo Of Lonsdale Street Showing Lanes Divided By...mentioning
confidence: 99%